THE REMAINS AND ARTIFACTS OF ANDALUSIAN-ISLAMIC CIVILIZATION IN SPAIN-VIII: NORTHESTERN SPAIN - Lütfi ŞEYBAN (Fırat University, 2019)
In the last century and today, in Spain or the Iberian Peninsula, nothing else left practically from Islamic heritage except several architectural works. Architectural works are in several cities (Cordoba, Granada and Seville). They are using as tourist attractions. The Mudéjar Style (Arte Mudejar) in architecture that caused by Islamic influence used in a lot of Spanish buildings. And should count the about four thousand Arabic words of Spanish in the Islamic heritage-listed from the past. In Al-Andalus has emerged a new style was born from harmonious blend of Mashreq-Maghreb-Iberian art. With the all kinds of motifs, patterns and decorations, this art is one of the most beautiful examples of Islamic art. Muslim and Christian architects and artists worked together to create this art. Mingling the Maghribi, Byzantine and European influences with Mashrik traditions emerged unique synthesis masterpieces. On top of specialities that makes Al-Andalus different from their counterparts and carry it further points there are certainly their their outstanding efforts in science, agriculture, and trade. Therefore, the regeneration of Spain came not hrough the northern barbarian tribes, but has from the south by the Muslim conquerors. This development was a civilization move much more than being a conquering. In this way, the most brilliant and developed civilization known during the Middle Ages of Europe was born in Spain in VIII-XVth centuries.